2014
DOI: 10.1002/2014gl059282
|View full text |Cite
|
Sign up to set email alerts
|

Systematic model forecast error in Rossby wave structure

Abstract: Diabatic processes can alter Rossby wave structure; consequently, errors arising from model processes propagate downstream. However, the chaotic spread of forecasts from initial condition uncertainty renders it difficult to trace back from root‐mean‐square forecast errors to model errors. Here diagnostics unaffected by phase errors are used, enabling investigation of systematic errors in Rossby waves in winter season forecasts from three operational centers. Tropopause sharpness adjacent to ridges decreases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
136
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(149 citation statements)
references
References 27 publications
(30 reference statements)
13
136
0
Order By: Relevance
“…These results are consistent with case study analysis of the relationship between diabatic processes in the WCB and upper-level flow (e.g., Stoelinga 1996;Grams et al 2011;. The representation of the upper-tropospheric circulation around ETCs has implications for downstream development of ETCs, Rossby waves and blocking (e.g., Chagnon et al 2012;Rodwell et al 2013;Gray et al 2014;Martínez-Alvarado et al 2015;Pfahl et al 2015). Any biases in this circulation may impact the ability of HiGEM to simulate ETCs at the eastern end of the storm tracks, such as those ETCs which affect Europe.…”
Section: Diabatic Tendencies and Pvsupporting
confidence: 81%
“…These results are consistent with case study analysis of the relationship between diabatic processes in the WCB and upper-level flow (e.g., Stoelinga 1996;Grams et al 2011;. The representation of the upper-tropospheric circulation around ETCs has implications for downstream development of ETCs, Rossby waves and blocking (e.g., Chagnon et al 2012;Rodwell et al 2013;Gray et al 2014;Martínez-Alvarado et al 2015;Pfahl et al 2015). Any biases in this circulation may impact the ability of HiGEM to simulate ETCs at the eastern end of the storm tracks, such as those ETCs which affect Europe.…”
Section: Diabatic Tendencies and Pvsupporting
confidence: 81%
“…It should be noted that this value of jet maximum represents a local wind speed value; nonlinear waves of realistic amplitude considerably reduce the zonal mean wind speed. A typical isentropic gradient of Ertel PV at the troposphere-stratosphere boundary to the northern side of wintertime ridges in analyses is 1.30 PVU per 100 km, and in 5-day forecasts is 1.05 PVU per 100 km (Gray et al 2014). Taking a typical PV contrast across the tropopause of 4 PVU therefore gives typical widths of the tropopause front on an isentropic surface of r 0 = 308 km and r 0 = 381 km in analyses and 5-day forecasts, respectively.…”
Section: Typical Dimensional Valuesmentioning
confidence: 89%
“…The magnitude of the smoothing error has recently been evaluated for several state-of-the-art weather forecast models by Gray et al (2014). They found that the decrease in the isentropic gradient of PV at the tropopause typically occurs during the 790 B. J. Harvey, J. Methven and M. H. P. Ambaum (0) from (3.34) and the phase and group speeds from (3.35) with wavenumber kL R = 1.…”
Section: Typical Dimensional Valuesmentioning
confidence: 99%
See 2 more Smart Citations